Production of hepatitis delta virus and suppression of helper hepatitis B virus in a human hepatoma cell line. - Wu, J C (1991)
The hepatitis delta virus (HDV) is a defective virus with a coat composing of the surface antigen of its helper virus, hepatitis B virus (HBV). Replication of HDV in the absence of HBV has been shown in cell cultures by transient transfection of the HDV plasmid. However, the formation and release of HDV virions have not been observed. In this report, a human hepatoma cell line HuH-7 was transiently cotransfected with HDV and HBV plasmids. The production of monomeric and multimeric antigenomic RNAs of HDV in the transfected cells indicated replication of the HDV genome. The major 3.5- and 2.1-kb RNAs of HBV were also expressed. Virions of both HDV and HBV were released from the cotransfected cells, as shown by the detection of monomeric genomic HDV RNA and partially double-stranded HBV DNA in the culture medium. Thus, this is the first report that describes the assembly and the release of HDV viral particles in an in vitro cell culture. The HDV virions released possessed physicochemical properties identical to those of the HDV virions found in infected human serum. Furthermore, expression of both the 3.5- and 2.1-kb RNAs of HBV was shown to be dramatically decreased by the presence of HDV, indicating suppression of the expression of HBV genes by HDV. The amount of HBV virions released was similarly suppressed by HDV. Cotransfection of HBV with an expression plasmid of the HDV delta antigen remarkably reduced the levels of the 3.5- and 2.1-kb HBV RNAs, indicating that suppression of the expression of HBV RNAs by HDV occurs via the action of the delta antigen. This HBV- and HDV-cotransfected human hepatoma cell line should provide an excellent system for the study of the function of the delta antigen and the interaction between HDV and its helper, HBV.